Pemberdayaan Masyarakat Perkotaan melalui Program Pelatihan Wirausaha Baru di Dinas Ketenagakerjaan Kota Bandung - Nuraini, Isyfi; Komariah, Siti; Abdullah, Mirna Nur Alia (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2026)
Rapid social and economic changes in urban areas have created employment challenges, particularly rising unemployment and limited absorption of labor in the formal sector. This study aims to analyze the community empowerment process through the New Entrepreneur Training Program organized by the Bandung City Manpower Office. A qualitative approach was used with data collected through interviews, observations, and documentation involving organizers, instructors, and participants. The findings show that the training improves participants’ capacity through entrepreneurial knowledge and skills, encourages active participation, fosters awareness of business opportunities, and expands access to information and institutional support. The program also encourages participants’ independence in starting small businesses, although wider information dissemination and stronger post-training assistance are still needed.